1998
DOI: 10.1038/1214
|View full text |Cite
|
Sign up to set email alerts
|

Positional cloning of the gene for X-linked retinitis pigmentosa 2

Abstract: X-linked retinitis pigmentosa (XLRP) results from mutations in at least two different loci, designated RP2 and RP3, located at Xp11.3 and Xp21.1, respectively. The RP3 gene was recently isolated by positional cloning, whereas the RP2 locus was mapped genetically to a 5-cM interval. We have screened this region for genomic rearrangements by the YAC representation hybridization (YRH) technique and detected a LINE1 (L1) insertion in one XLRP patient. The L1 retrotransposition occurred in an intron of a novel gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
275
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(282 citation statements)
references
References 33 publications
4
275
0
Order By: Relevance
“…They are important for the maintenance of photoreceptor cells, since knockouts of Arl3 or HRG4 cause strong retinal defects in mice and mutations of RP2 are causing retinitis pigmentosa [18,19,30]. The Arl3 À/À deletion mice exhibit a mislocalization of rhodopsin and probably also other proteins that are important for phototransduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are important for the maintenance of photoreceptor cells, since knockouts of Arl3 or HRG4 cause strong retinal defects in mice and mutations of RP2 are causing retinitis pigmentosa [18,19,30]. The Arl3 À/À deletion mice exhibit a mislocalization of rhodopsin and probably also other proteins that are important for phototransduction.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the proposed Arl3 effector RP2 is actually a highly efficient and specific Arl3GAP with only limited activity on Arl2 [9]. RP2 is a protein mutated in patients with X-linked retinitis pigmentosa 2 [19] and displays sequence and functional homology to CoC.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of linkage analyses, the frequency of RP3 as a fraction of XLRP is 56 to 90%, and RP2 accounts for most of the remainder Ott et al, 1990;Teague et al, 1994;Bergen et al, 1995;Fujita et al, 1997]. Cloning of RP2 in Xp11.23 [Schwahn et al, 1998] (MIM# 312600) and subsequent mutation analysis have confirmed that RP2 accounts for 10 to 25% of XLRP. Two other XLRP loci have been mapped in single pedigrees: RP23 at Xp22 (GDB# 9837371) and RP24 at Xq26-27 [Gieser et al, 1998] (MIM# 300155).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this view, a TBCC-related protein called retinitis pigmentosa 2 protein (RP2) localizes at the basal body of Trypanossoma brucei flagellum, where it was proposed to participate in a tubulin quality control mechanism prior to incorporation of tubulin heterodimers in the axoneme (108). In vertebrates, RP2 has been extensively studied due to its involvement in the X-linked condition retinitis pigmentosa, a pathology characterized by a progressive degeneration of photoreceptor cells (109,110). Similar to TBCC, RP2 also contains a TBCC and a CARP domain in its N-terminal region, suggesting a possible functional overlap between these two proteins.…”
Section: The Ciliary Roles Of Tubulin Folding Pathway Members and Relmentioning
confidence: 98%